The Role Of Instagram Promotions And Taste On Customer Satisfaction Mediated By Purchasing Decisions At Tetufresh - Nurhudi Slamet; Elimwaty Rombe; Rosida P. Adam; Mohammad Zeylo Auriza (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of promotion through Instagram and taste on customer satisfaction mediated by purchasing decisions at Tetufresh in Palu City. The population of this study are customers who often use the Instagram Platform and have purchased Tetufresh products with a sample size of 120 respondents. The technique in collecting this data uses a Google Form-based questionnaire. The technique in this sampling uses purposive sampling. The technique in analyzing the data of this study uses Stuructural Equation Modeling (SEM) with SmartPLS software. The results of this study indicate that social media promotion has a positive effect on customer satisfaction, social media promotion has a positive effect on purchasing decisions, Taste has a positive effect on customer satisfaction, Taste has a positive effect on purchasing decisions, purchasing decisions have a positive effect on customer satisfaction, Instagram promotion mediated Purchasing decisions have a positive effect on customer satisfaction, Taste mediated Purchasing decisions have a positive effect on customer satisfaction.